2020
DOI: 10.1111/rda.13855
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with ewe and lamb survival, and subsequent reproductive performance of sheep undergoing emergency caesarean section

Abstract: Clinical records of all 212 ewes undergoing emergency caesarean surgery at a veterinary teaching hospital between January 2008 and December 2019 were evaluated retrospectively. Their age ranged from 1 to 10 years (median = 4 years), with German merino the predominant breed (48.1% of cases). The most frequently diagnosed indications were insufficient cervical dilatation (n = 94, 44.3%), uterine torsion (n = 50, 23.6%), foetopelvic disproportion (n = 31, 14.6%) and vaginal prolapse intra partum (n = 11, 5.2%). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Some cases of foetal malformation were also observed (9/95, 9.5%). Dystocia was resolved by manual correction in 71 of the 302 cases (23.5%), while 225 animals (74.5%) were treated by caesarean section as previously described (Voigt et al., 2021). A partial foetotomy (Winter, 1999) was performed in six ewes (2.0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases of foetal malformation were also observed (9/95, 9.5%). Dystocia was resolved by manual correction in 71 of the 302 cases (23.5%), while 225 animals (74.5%) were treated by caesarean section as previously described (Voigt et al., 2021). A partial foetotomy (Winter, 1999) was performed in six ewes (2.0%).…”
Section: Resultsmentioning
confidence: 99%
“…Maternal causes of dystocia are therefore often the leading causes reported in these study types (Brounts et al., 2004; Ennen et al. 2013; Sobiraj, 1994; Voigt et al., 2021). Among maternal causes of ovine dystocia, incomplete cervical dilatation is the most frequently reported problem, while other causes such as uterine torsion are considered rare in sheep (Jacobson et al., 2020; Parkinson et al., 2019a, b; Winter, 1999) in contrast to other ruminants.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, in Germany, application of non-steroidal anti-inflammatory drugs (NSAIDs) in sheep require drug repurposing from other species. Voigt et al found that most ewes are presented for SC due to insufficient cervical dilatation (44.3%) [ 4 ]. Maternal survival rate was described as 97.8% under field conditions [ 4 ] and in studies comparing elective SC to vaginal delivery, postnatal deaths in ewes are similar [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Voigt et al found that most ewes are presented for SC due to insufficient cervical dilatation (44.3%) [ 4 ]. Maternal survival rate was described as 97.8% under field conditions [ 4 ] and in studies comparing elective SC to vaginal delivery, postnatal deaths in ewes are similar [ 5 ]. In ewes presented at a veterinary teaching hospital, ewe mortality up until hospital discharge was 10.8%, as survival rate is mostly influenced by delayed presentation to a veterinarian [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation